(untitled) (Dentika: Dental Journal, 2025)
Clear aligners are gaining popularity as an alternative to conventional fixed orthodontic appliances in orthodontic treatment due to the aesthetic appeal and comfort. Therefore, this scoping review aimed to discuss the current state of aesthetical value, clinical efficacy, material, and limitations of clear aligners in orthodontic treatments compared to fixed orthodontic appliances. A systematic search was conducted across PubMed, ScienceDirect, EBSCOHost, and Google Scholar, resulting in 657 articles, and only 19 met the inclusion criteria for in-depth analysis. The result showed that clear aligners, particularly Invisalign, are effective for mild to moderate malocclusions, offering enhanced aesthetics and increased patient satisfaction. However, these appliances are less effective than traditional braces in achieving precise tooth movements, such as occlusal adjustments and torque control. Advances in aligner materials, such as improved elasticity and reduced biofilm accumulation showed great potential but are limited by the amount of study found. In addition to the aesthetical value, clear aligners provide better treatment outcomes than fixed orthodontic appliances depending on the complexity of the malocclusion being treated.